Seroprevalence of economically important viral pathogens in swine populations of Trinidad and Tobago, West Indies - Sookhoo, Jamie R. V. (Trop Anim Health Prod, 2017)
The objective of this study was to evaluate the seroprevalence and identify the strains of swine influenza virus (SwIV), as well as the seroprevalence of porcine parvovirus (PPV), transmissible gastroenteritis virus (TGEV), porcine reproductive and respiratory syndrome virus (PRRSV), porcine respiratory coronavirus (PRCV), porcine circovirus type 2 (PCV-2), and classical swine fever virus (CSFV) in pigs in Trinidad and Tobago (T&T). Blood samples (309) were randomly collected from pigs at farms throughout T&T. Serum samples were tested for the presence of antibodies to the aforementioned viruses using commercial ELISA kits, and the circulating strains of SwIV were identified by the hemagglutination inhibition test (HIT). Antibodies against SwIV were detected in 114 out of the 309 samples (37%). Out of a total of 26 farms, 14 tested positive for SwIV antibodies. HI testing revealed high titers against the A/sw/Minnesota/593/99 H3N2 strain and the pH1N1 2009 pandemic strain. Antibodies against PPV were detected in 87 out of the 309 samples (28%), with 11 out of 26 farms testing positive for PPV antibodies. Antibodies against PCV-2 were detected in 205 out of the 309 samples tested (66%), with 25 out of the 26 farms testing positive for PCV-2 antibodies. No antibodies were detected in any of the tested pigs to PRRSV, TGEV, PRCV, or CSFV.